Erişkin kistik fibrozis olgusu - (:unkn) unknown (My University, 2005)
Kistik fibrozis (KF) beyaz ırkta en çok görülen otozomal resesif geçişli kalıtsal hastalıktır. KF’li hastalarda akciğer komplikasyonları halen esas morbidite ve mortalite nedeni olmakla birlikte, hastaların yaşam sürelerinin uzamasıyla pankreatik yetmezlik, biliyer siroz ve gastrointestinal sistem problemleri daha sık görülmektedir. Bu yazıda, tekrarlayan akciğer infeksiyonları ve malabsorpsiyonu olduğu halde, erişkin yaşta tanı alan, diabetes mellitus’u olan ve safra taşı ve ağır kolestaz bulguları geliştiren bir erişkin KF hastası sunulmuştur. Ülkemizde KF’li erişkin hastaların sayısı giderek artmaktadır. Bu nedenle, özellikle erişkin dönemde sık karşılaşılan diabetes mellitus, karaciğer hastalığı ve ilişkili komplikasyonların erken dönemde tanı ve tedavi alabilmesi için hem çocuk hem de erişkin hekimlerinin KF ile ilgili bilgi ve deneyimlerinin artırılmasının uygun olacağı kanısındayız.

Cystic fibrosis (CF) is the most common autosomal recessively inherited disease of the Caucasians. Although the pulmonary complications are the main cause of morbidity and mortality in CF, pancreatic insufficieny, biliary cirrhosis and gastrointestinal system problems are seen more commonly as the life expectancy of CF patients increases. We present a case who was diagnosed with CF during adulthood despite his symptoms with recurrent bronchopulmonary infections and malabsorption since infancy. This patient also had CF related diabetes mellitus and severe cholestasis and gallstones. The number of CF patients surviving into adulthood is increasing in our country. It is important for both the pediatricians and adult physicians to gain experience in CF so that diabetes mellitus, hepatobiliary disease and its complications seen mostly during adulthood of these patients could be diagnosed and treated earlier.
An adult case of cystic fibrosis
Keywords: Genel ve Dahili Tıp; Pediatri